ROLE AND IMPORTANCE OF MODALITY IN MODERN MEDIA - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
In our article, Scientists ' views on the interconnection of art over the centuries and the concepts of multimodality are studied, while the roots of this new plant have grown on different soils; social semiotics, pedagogy, medicine and Linguistics, and Communication Sciences as well.